2022
DOI: 10.1002/rra.3915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of an electric barrier on fish entrainment in an irrigation canal in Colorado

Abstract: Entrainment of fish in irrigation canals is a source of mortality for sport and native fishes and can affect populations and species diversity. To reduce entrainment of wild trout, an electric barrier was installed on the South Canal, an irrigation ditch on the Gunnison River in western Colorado, USA. The objective of this study was to evaluate the effectiveness of the barrier by marking fish upstream of it and estimating fish populations in the canal downstream before and after the barrier was operational. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This supports our hypothesis that Murray Cod stocked nearby pump intakes are susceptible to entrainment. This finding is consistent with some American studies which have shown entrainment of stocked salmonids at water diversions (Simpson & Ostrand 2012;Kowalski et al 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This supports our hypothesis that Murray Cod stocked nearby pump intakes are susceptible to entrainment. This finding is consistent with some American studies which have shown entrainment of stocked salmonids at water diversions (Simpson & Ostrand 2012;Kowalski et al 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with some American studies which have shown entrainment of stocked salmonids at water diversions (Simpson & Ostrand 2012; Kowalski et al . 2022).…”
Section: Discussionmentioning
confidence: 99%